APPLICATION OF INVERSE DISTANCE WEIGHTED (IDW) INTERPOLATION IN DETERMINING WAVE HEIGHT IN THE WATERS OF THE SUNDA STRAIT: PENERAPAN INTERPOLASI INVERSE DISTANCE WEIGHTED (IDW) DALAM MENENTUKAN TINGGI GELOMBANG LAUT DI PERAIRAN SELAT SUNDA - Willdan Aprizal Arifin; Anton Daud; Ramzan Pradana Maulsyid; Raisa Maulidia; Lukman Handyanto; Rifki Andreana Sutrisno (Jurnal Teknologi Perikanan dan Kelautan, 2025)
The Sunda Strait is one of the busiest transportation routes in Indonesia, which has great potential in the fields of shipping, fisheries, and tourism. In addition to its potential, the Sunda Strait is also faced with challenges in the form of high wave risks that can jeopardize safety and disrupt the smooth running of maritime activities. The availability of wave data is an important aspect in maintaining safety and maritime activities. This research aims to visualize Inverse Distance Weighted (IDW) interpolation of wave height to provide more accurate and detailed information in the waters of the Sunda Strait for the benefit of the maritime sector. In this study, the IDW method was applied to wind data at three Automatic Weather Stations (AWS) points around the Sunda Strait region. Before the application of IDW, the Delaunay Triangulation method was used to ensure the optimization of sample points used to perform interpolation. The results showed that the significant wave height tended to be higher in the southwest monsoon than in the northeast monsoon. During the observation period 2022-2024, the maximum significant wave height was recorded at 2.06 meters, and the minimum one was close to zero. The application of the IDW method successfully visualizes the spatial distribution of wave height in detail, thereby supporting decision-making in risk mitigation and shipping safety in the Sunda Strait.